Stereotypy - komunikacja - literatura - Grochowski, Grzegorz (Przestrzenie Teorii, 2007)
The article presents an attempt to establish what role is played by stereotypes within the process of literary communication. The main framework for the presented argumentation is based on the cognitivist approach. The "stereotypes" are defined as clusters of evaluative, but - against the background of the common concept - not necessarily negative, social judgements, beliefs and attitudes. They can be employed in literary studies as long as they are described more explicitly as semantic representations. The next claim is that stereotypical beliefs are organized as the sets of propositions which receive specific referential status within specific contextual employment. Literature can be analysed as one of the important social fields of such acquisition.